Sustainability analysis of family farming in an agroforestry system in Alagoa Nova (Research, Society and Development, 2020)
In the municipality of Alagoa Nova, a swamp in Paraíba, vegetable and fruit crops predominate where, despite the existence of information on agroecological practices, a large part of the properties use traditional management with an exaggerated use of pesticides. In this sense, the present work aimed to investigate, discuss and analyze agricultural sustainability through social, environmental and economic indicators of Granja Betel, in the production of the following agricultural crops: corn, beans, cassava and sweet potatoes in the municipality of Alagoa Nova - PB. For this, the MESMIS method was used. The evaluation of the method's structure occurs in a spiral way, so that there can be a process of continuous evaluations, in this evaluation system the indicators play a main role, leading to obtaining data for later measurement of sustainability, it also indicates necessary changes and paths to be taken. followed to contribute to the sustainable framework in agro-ecosystems. 78.94% of the indicators are in ideal situations. The result shows that most of the indicators on the property are in ideal situations, thus showing a management close to adequate sustainability.